The Senseless Machine: Toward a Crip Reading of (No-touch) Hands and Human Value from Eugenics to Biometrics (Sociologisk Forskning, 2025)
Combining crip theory and existential media studies, the purpose of this theoretical essay is to critically interrogate a biometric palm-reading device that turns the hand into a means for payment – connecting its datafied veins to one’s assets – by unpacking its specific “techno-logics” and probing its forceful yet ambivalent sociotechnical imaginary. Palm recognition technology relies on the annulment of touch which calls forth, and depends on, what we call the existential–phenomenological chasm. The argument is that as hands are reduced to touch-free functionalist components, the realities of the embodied existential self are made invisible, and so is a fuller perceptual field of being human in diversity and disability. The chasm thus reinforces the ableism of the normate, instrumental hand, while also invoking dark genealogies of measuring bodies in culture. We caution that if biometrics were to be turned into a primary signifier of human identity and value ascription, this would reactivate eugenic hauntings with consequences for “human value”. This fact calls for “cripping” the senseless machine, subjecting it to the crucial work of crip technoscience.